2014
DOI: 10.1186/1758-5996-6-48
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of both fasting and postprandial glycemic control by the two-step addition of miglitol and mitiglinide to basal insulin therapy: a pilot study

Abstract: BackgroundCombination therapy consisting of basal insulin and oral hypoglycemic agents (OHAs) is effective for the treatment of type 2 diabetes (T2DM) that cannot be adequately controlled using OHAs alone. Though basal insulin with metformin or sulfonylurea is an effective therapy, it cannot reduce postprandial glycemia without the risk of hypoglycemia. We examined a two-step regimen consisting of the addition of postprandial hypoglycemic agents (an alpha-glucosidase inhibitor and a glinide) in patients whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Both cases result in an elevated concentration of blood glucose. Specifically, postprandial (i.e., after-meal) hyperglycemia is commonly defined as a blood glucose level greater than 180 mg/dL two hours after a meal . Chronic high blood glucose levels lead to pathological complications, including cardiovascular diseases, stroke, and potential nontraumatic limb amputations, as well as microvascular complications leading to kidney diseases, blindness, and neuropathy. , Thus, tight glucose control in diabetic patients which can prevent, or at least delay, the onset of its late complications is of enormous importance and has been the subject of extensive research efforts over the years .…”
mentioning
confidence: 99%
“…Both cases result in an elevated concentration of blood glucose. Specifically, postprandial (i.e., after-meal) hyperglycemia is commonly defined as a blood glucose level greater than 180 mg/dL two hours after a meal . Chronic high blood glucose levels lead to pathological complications, including cardiovascular diseases, stroke, and potential nontraumatic limb amputations, as well as microvascular complications leading to kidney diseases, blindness, and neuropathy. , Thus, tight glucose control in diabetic patients which can prevent, or at least delay, the onset of its late complications is of enormous importance and has been the subject of extensive research efforts over the years .…”
mentioning
confidence: 99%
“…Furthermore, in this analysis, pre‐prandial hyperglycemia was improved, as well as post‐prandial hyperglycemia, in the COMB group. It is well known that alpha‐glucosidase inhibitors 36 and glinide 37 acting directly on postprandial hyperglycemia also improved pre‐prandial hyperglycemia. DPP‐4 inhibitors that improved postprandial hyperglycemia on glycemic responsiveness also improve the next pre‐prandial glucose level 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have assessed the effects of oral postprandial hypoglycemic agents used in combination with basal therapy. We previously reported that a 2-step regimen consisting of the addition of the postprandial hypoglycemic agents miglitol and mitiglinide to basal insulin therapy enabled more than 80% of the patients to achieve a good glucose profile [ 11 ]. CGM also showed the effectiveness of miglitol and mitiglinide in lowering the daytime blood glucose levels without inducing hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the 2-step addition of 2 postprandial hypoglycemic agents, an alpha-glucosidase inhibitor and a glinide, to basal insulin therapy was potentially effective and safe for decreasing both the fasting and postprandial glucose levels [ 11 ]. While these basal insulin therapies are commonly used for patients with insufficient glycemic control using only OHAs, which OHAs are the most efficient for use in combination with basal insulin therapy remains unclear.…”
Section: Introductionmentioning
confidence: 99%